Medición de genotoxicidad cromosomática de meristemos de Eucaplytus glóbulus labill inducidas por cafeína y carbetamida - Palacios Morales, Félix Nicolás (2019)
Objective: Describe the chromosomal genotoxicity Eucalyptus globulus Labill meristems induced by caffeine andthe aberrations caused carbetamida in each mitotic phase. Methodology: Seeds sown in sterile Petri dishes with 20seeds per seven days of germination, the roots reach a length of one to two centimeters disinfected in bleach solution - distilled water (3:1). After germination treatments applied caffeine four hours and twelve of recovery, in thecase of one hour of treatment carbetamida no downtime. Results: We determined the mitotic process of Eucalyptusglobulus radical cells susceptible to caffeine and carbetamida. The research was carried out in selected rootlets ofseedlings with more vigor and growth in petri dishes 20 cm in diameter in the biology lab. The technique of crushingand staining with hydrochloric acetorceína mitotic analysis, studying an average of 1051.5 cells / plant. Taking 0.2mm from the growth region. The root cuttings were made every hour for 24 hours. Most mitotic cells were observedin roots collected between 6:00 to 9:00 a.m. which recorded the highest mitotic index (MI) of 87.34% and 79.71%).For the different stages of mitotic phase The study indicated that the prophase were in higher proportion (87.34%and 69.71%), followed by metaphase (4.08% and 4.98%), anaphase (3.67% and 8.54%) and telophase (4.89 % and6.76%, respectively) between treatments with caffeine and carbetamida cells.Conclusion: The study of mitotic stages, said the index scale aberrant profásico two similar proportion carbetamida presented followed by metaphase,anaphase and telophase, indicates cellular sensitivity to the chemical action of the drug in the period that inhibitsproliferative meristematic cell division generates binucleated and multinucleated.